International Cooperation and Indonesia’s Geopolitical Perspective in Indo-Pacific - Rosdiana, Hesti (Jurnal Ilmiah Hubungan Internasional, 2024)
This paper emphasizes the analysis of Indonesia's geopolitical perspective through international cooperation that is part of Indonesia's geopolitics in the Indo-Pacific region. The results of this paper explain that Indonesia's geopolitical interests cannot be separated from the importance of building mutual trust, as well as regional development through international cooperation for global interests. In other words, regional development through international cooperation will increase regional stability so as to encourage various economic, political and security activities that not only reduce political friction, but also provide strategic advantages for every actor who has an interest in the Indo-Pacific. Keywords: Indonesia, Geopolitics, Indo-Pacific, international cooperation